Do Satisfaction and Variety Seeking Tendency Affect Revisit Intention in Local Coffee Shop Chain? - Tirus, Hilman Madani; Nuralam, Inggang Perwangsa (Faculty of Business and Economics Universitas Atma Jaya Yogyakarta, 2025)
The purpose of this study was to provide an insight into the crucial antecedents of customer satisfaction and revisit intention in the context of local coffee shop chain customers in Malang City. Studies on customer satisfaction and revisit intention have been conducted extensively by previous researchers. However, this study addresses existing gaps by identifying specific antecedents of customer satisfaction (service quality, atmosphere, and convenience) and revisit intention (customer satisfaction and variety seeking tendency), and analyzing their relationships within a single structural equation model. The type of research used is explanatory research using a quantitative approach. The population of this study were customers of the local coffee shop chain in Malang City. The sampling technique in this study was non-probability sampling using purposive sampling. The sample used in this study amounted to 232 respondents. The analysis method used is the Structural Equation Model based on Partial Least Square (SEM-PLS). The results of this study indicate that service quality and atmosphere affect customer satisfaction. While convenience has no effect on customer satisfaction. Customer satisfaction and variety seeking tendency affect revisit intention.